First, do no harm: Generalized procreative non‐maleficence. (September 2017) - Saunders, Ben
Abstract: New reproductive technologies allow parents some choice over their children. Various moral principles have been suggested to regulate such choices. This article starts from a discussion of Julian Savulescu's Principle of Procreative Beneficence (PPB), according to which parents ought to choose the child expected to have the best quality of life, before combining two previously separate lines of attack against this principle. First, it is suggested that the appropriate moral principles of guiding reproductive choices ought to focus on general wellbeing rather than prioritizing that of the child and, second, that they ought to be non‐maximizing (e.g. seeking the 'good enough' or to avoid harm). Though neither of these suggestions is entirely novel, combining them results in a new, and arguably more plausible, principle to regulate procreative choices, which I call the Principle of Generalized Procreative Non‐Maleficence (PGPNM). According to this principle, the primary obligation on parents is not to cause harm to other people through their reproductive choices.